Enhancing financial awareness and taxation for Creative Space Community - Nur Chayati; Khresna Bayu Sangka; Estetika Mutiaranisa Kurniawati; Nurmadi Harsa Sumarta; Agung Nur Probohudono; Saktiana Rizki Endiramurti; Anita Zulfiani; Anis Widjajanto (Community Empowerment, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have been recognized as crucial components and dynamic driving forces for various economies. The Indonesian government has paid serious attention to the MSME sector. One of the strategies for developing MSMEs to upgrade is through increased access to financing. However, the serious attention from the Indonesian government has not been maximized by MSMEs because it is not balanced with the ability related to financial management and taxation. Creative Space is an MSME Community, most of whose members are start-up companies that still lack knowledge of finance and taxation. The purpose of this community service is to provide financial education and tax obligations for Creative Space members. The method used is by providing guidance in preparing financial statements and tax reports. The results of the implementation of this financial and tax education are that all members of Creative Space can prepare financial statements and report the tax obligations that must be fulfilled by MSMEs.